The Information Technology Manager as an agent of transformation in companies (Research, Society and Development, 2024)
This article explores the relevance of the Information Technology (IT) Manager as a transformation agent within organizations. The objective of this study IT Managers align technological resources with business needs, promoting innovation and efficiency. The research employed a mixed-methods approach, which included a literature review, data collection through online questionnaires, and analysis of the results. Data were collected from IT professionals in small and medium-sized enterprises, and the results indicate that 100% of respondents consider the IT Manager essential for organizational success. In addition to implementing technologies, this professional is responsible for fostering an innovative environment where experimentation and creative thinking are encouraged. The absence of an IT Manager can lead to project failures and missed innovation opportunities, underscoring the importance of strategic alignment between IT and business objectives. The article concludes that the role of the IT Manager is crucial for maximizing resources and optimizing processes, allowing organizations to quickly adapt to market changes and maintain competitiveness.